Peningkatan Mutu Fungsional Kombucha dengan Penambahan Kunyit sebagai Sumber Antioksidan dan Pewarna Alami - Fauzi, Mukhammad; Azmiyah, Mafazatul; Bakri, Abi (Fakultas Teknologi Pertanian Universitas Jember, 2025)
Turmeric is a rhizome known to contain high levels of curcumin. It’s primarily processed into traditional beverages such as herbal medicine (jamu) ready to drink or its instant powder. Turmeric can be used to make a contemporary fermented beverage, i.e. kombucha. This study aims to determine the effect of adding turmeric and fermentation time in improving the quality of antioxidant properties and natural color as well as the physical, chemical, and sensory properties of turmeric kombucha. Unpeeled turmeric was washed and sliced, and then kombucha was made with concentrations of 4%, 6%, and 8% turmeric (w/v) in 500 mL of a 10% sugar solution. This mixture was boiled for 10 minutes, then filtered and cooled to 29–30°C. Then, 10% SCOBY starter was added and fermented for 6, 8, 10, and 12 days. Parameters such as antioxidant activity lightness, yellowness, total solids, pH, total titratable acid, and organoleptic properties were measured. Parameters such as antioxidant activity, lightness, yellowness, total solids, pH, total titratable acid, and organoleptic properties were measured. The percentage of turmeric and fermentation time significantly affected the quality of antioxidant activity against DPPH, color brightness value, yellowness value, pH, total titratable acid, and, as well as panelists' preference for the organoleptic properties of turmeric kombucha. Effectively, turmeric kombucha drink made from 6% turmeric and fermented for 8 days was characterized by antioxidant activity of 71.27%, brightness of 67.67, total soluble solids of 12.19%, pH 3.52, total titratable acid of 0.41%, and overall preference value of 5.63 (like). In the future, turmeric kombucha can be consumed as a functional kombucha-based beverage. Keywords: antioxidant activity, curcumin, turmeric, kombucha, sensory